Heart rate variability, exercise capacity and levels of daily physical activity in children and adolescents with mild-to-moderate cystic fibrosis - Pitiguara de Freitas Coelho; Roberta Ribeiro Batista Barbosa; Rodrigo dos Santos Lugao; Fernanda Mayrink Gonçalves Liberato; Pâmela Reis Vidal; Roberta de Cássia Nunes Cruz Melotti; Márcio Vinícius Fagundes Donadio (World Scientific Publishing, 2022)
Background: Autonomic nervous system balance is altered in cystic fibrosis (CF), although its influence on physical fitness has been poorly explored. Objective: This study aimed to evaluate the association of heart rate variability (HRV) with exercise capacity and levels of daily physical activity in children and adolescents with mild-to-moderate CF. Methods: A cross-sectional study including individuals with CF aged 6-18 years, not under CFTR modulator therapy, was performed. Sociodemographic (age, sex) and clinical information (airway colonization, pancreatic insufficiency, and genotyping) were collected. In addition, exercise capacity (modified shuttle test - MST), lung function (spirometry), body composition (bioimpedance), levels of daily physical activity (5-day accelerometer), and HRV (both at rest and during the MST) were evaluated. Results: 30 individuals (20 females) aged [Formula: see text] years, mean FEV[Formula: see text]%, were included. A sympathovagal balance (LF/HF) increase ([Formula: see text]) during the MST was shown, indicating a predominance of sympathetic modulation. The standard deviation of all RR intervals (SDNN) and the high frequency (HF) index during exercise correlated significantly with FEV1 ([Formula: see text], [Formula: see text] and [Formula: see text], [Formula: see text]; respectively). MST distance also correlated positively and significantly with SDNN ([Formula: see text], [Formula: see text]), square root of the mean of the sums of squares of frequencies between RR intervals greater than 50[Formula: see text]ms - RMSSD ([Formula: see text], [Formula: see text]), low frequency - LF ([Formula: see text], [Formula: see text]), HF ([Formula: see text], [Formula: see text]), dispersion of points perpendicular to the short-term identity line - SD1 ([Formula: see text], [Formula: see text]) and negatively with LF/HF ([Formula: see text], [Formula: see text]). Regarding daily physical activity, SDNN at rest ([Formula: see text], [Formula: see text]) and exercise ([Formula: see text], [Formula: see text]) showed positive correlations with time in moderate-to-vigorous activities. When normalizing the SDNN and classifying individuals as normal or altered, those presenting altered SDNN showed poorest FEV1 ([Formula: see text]) and lower exercise capacity ([Formula: see text]). Conclusion: HRV correlates with lung function, exercise capacity and levels of daily physical activity in children and adolescents with CF. The study highlights the influence of CF on autonomic function and suggests HRV measurement as an easy tool to be used in clinical settings as an alternative marker to monitor CF individuals.